The Charge Storage Mechanisms of 2D Cation‐Intercalated Manganese Oxide in Different Electrolytes. Issue 3 (29th November 2018) - Zhang, Qingnuan; Levi, Mikhael D.; Dou, Qingyun; Lu, Yulan; Chai, Yinguang; Lei, Shulai; Ji, Hengxing; Liu, Bao; Bu, Xudong; Ma, Pengjun; Yan, Xingbin
Abstract: 2D ion‐intercalated metal oxides are emerging promising new electrodes for supercapacitors because of their unique layered structure as well as distinctive electronic properties. To facilitate their application, fundamental study of the charge storage mechanism is required. Herein, it is demonstrated that the application of in situ Raman spectroscopy and electrochemical quartz crystal microbalance with dissipation monitoring (EQCM‐D), provides a sufficient basis to elucidate the charge storage mechanism in a typical 2D cation‐intercalated manganese oxide (Na0.55 Mn2 O4 ·1.5H2 O, abbreviated as NMO) in neutral and alkaline aqueous electrolytes. The results reveal that in neutral Na2 SO4 electrolytes, NMO mainly displays a surface‐controlled pseudocapacitive behavior in the low potential region (0–0.8 V), but when the potential is higher than 0.8 V, an intercalation pseudocapacitive behavior becomes dominant. By contrast, NMO shows a battery‐like behavior associated with OH − ions in alkaline NaOH electrolyte. This study verifies that the charge storage mechanism of NMO strongly depends on the type of electrolyte, and even in the same electrolyte, different charging behaviors are revealed in different potential ranges which should be carefully taken into account when optimizing the use of the electrode materials in practical energy‐storage devices. Abstract : A molecular‐level understanding of the charging mechanisms for 2D cation‐intercalated manganese oxide, by using operando Raman spectroscopy and an electrochemical quartz crystal microbalance with dissipation monitoring. The results show the charge storage mechanism of Na0.55 Mn2 O4 ·1.5H2 O strongly depends on the type of electrolyte, and even in the same electrolyte, different charging behaviors are revealed in different potential ranges.